Design and implementation of the new Italian healthcare digital interoperable registry for implantable medical devices. (29th July 2022) - Bacocco, Duilio Luca; Carrani, Eugenio; Ciciani, Bruno; Di Sanzo, Pierangelo; Leotta, Francesco; Torre, Marina
Abstract: Nowadays, the role played by registries in monitoring and improving healthcare, including the quality of medical devices, is widely recognized. A well‐designed digital healthcare registry, in particular regarding data collection procedures and tools, can effectively support goals such as monitoring a (large) population subject to a specific condition, describing the natural history of diseases, supporting observational study methods, as well as evaluating the clinical effectiveness or cost effectiveness of healthcare products and services. This article describes the architecture of a new platform implementing a digital interoperable healthcare registry, the Italian Implantable Prostheses Registry (RIPI). One of the main goals of RIPI is to provide reliable and high‐quality data for monitoring surgery outcomes, performing survival analysis, assessing the safety of devices and procedures, and supporting the traceability of patients. The article focuses on the key aspects and choices that guided the design and implementation processes of the new platform. Most of the design choices came from specific requirements to fulfill, in particular concerning data quality, access policy, interoperability, extensibility and modularity. Overall, the article discusses the main challenges and the adopted solutions, proposing a design perspective and describing an experience of interest for computer scientists, engineers and practitioners, in particular in the area of healthcare information systems.